Correlation between disruptive behaviors and school grouping (single-sex vs. coeducational) in students from Callao, Peru - Gordillo, Enrique G. (2013)
Debate on single-sex vs. coeducational schooling has increased over the last years. The purpose of the following study is to produce empirical evidence on this debate by comparing the frequency of disruptive behaviors in students thatattend single-sex and coeducational schools, in order to find statistical correlation.The frequency of disruptive behaviors in students coming from 5 single-sex schools was compared to that coming from 5 coeducational ones. Data came from 844 students aged 14, attending public schools in Callao, Peru. Students from single-sex schools showed less frequent disruptive behavior in each of the three measured categories—disruptive behaviors, behaviors that show lack of responsibility and anti-social behavior. A weak correlation was found between each of the three categories and the main variable. The study controlled for extraneous variables.